PERANCANGAN KONTEN INSTAGRAM AMY WONG DI BURO CREATIVE STUDIO SEBAGAI IMPLEMENTASI PROGRAM MBKM MAGANG/PRAKTIK KERJA - Wiryawan, Adelya; Arya Putraka, Agus Ngurah; Julianto, I Nyoman Larry (AMARASI: JURNAL DESAIN KOMUNIKASI VISUAL, 2024)
The design of Amy Wong's Instagram content at Buro Creative Studio is a form of implementation of the MBKM Internship/Work Practice program which is in line with the general guidelines of the MBKM program of the Indonesian Institute of the Arts Denpasar which refers to Permendikbud No. 3, 2020. The purpose of this research is to add insight and experience directly in the industry field relevant to the visual communication design department and to know more about the process of designing social media content especially Instagram. Buro Creative Studio, which was established in 2017, was chosen as a partner in this program because of its scope that is in line with the visual communication design department, namely branding, marketing, and social media content. The study lasted for 4 months, from February to June. The research was conducted using observation, interview, literature, and documentation methods. The result of this research is to know more about Amy Wong's Instagram content design management at Buro Creative Studio and to know the process of Buro Creative Studio creating Instagram content design for Amy Wong. The Instagram content produced is in the form of Instagram highlight icons and Instagram stories, as well as supporting media in the form of bag designs, stickers, and greeting cards.